2016
DOI: 10.1111/bdi.12445
|View full text |Cite
|
Sign up to set email alerts
|

Differential neurometabolite alterations in brains of medication‐free individuals with bipolar disorder and those with unipolar depression: a two‐dimensional proton magnetic resonance spectroscopy study

Abstract: These results add to the evidence of brain metabolite differences in brains of patients with UD and BD which may be of help in differentiating these two mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…Psychotropic medication may have affected a few clusters, but the majority of the observations are likely independent of the medication. The clusters that reveal significant alterations in the DKI indices in this study are known to play a role in mood regulation, and abnormalities in these regions have been reported in affective disorders . The results of this study are thus thought to support the existing evidence about neural underpinnings associated with these affective disorders.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Psychotropic medication may have affected a few clusters, but the majority of the observations are likely independent of the medication. The clusters that reveal significant alterations in the DKI indices in this study are known to play a role in mood regulation, and abnormalities in these regions have been reported in affective disorders . The results of this study are thus thought to support the existing evidence about neural underpinnings associated with these affective disorders.…”
Section: Discussionsupporting
confidence: 82%
“…A positive correlation between the plasma cortisol level and serotonin transporter availability has been observed in the caudate nucleus and midbrain in MDD, but not in BD . Lower concentrations of choline and creatine compounds and N‐acetyl aspartate have been reported in the parietal cortex of BD patients and posterior cingulate cortex of MDD patients . Third, the findings of neuroimaging studies also suggest differences in cortical thickness, functional connectivity, and cerebral blood flow in the frontal, parietal, and temporal lobes between these two disorders .…”
mentioning
confidence: 98%
“…Although several studies in persons with depression have reported no difference in total creatine concentrations ([tCr]), which include concentrations of both creatine ([Cr]) and phosphocreatine ([PCr]), in multiple brain regions [113,114,115,116,117,118,119,120,121,122], others indicate increased [tCr] in some regions, such as in the inferior prefrontal white matter (WM) [123] and left caudate [124]. Studies have shown reduced [tCr] in MDD in the left dorsolateral prefrontal cortex (PFC) [125], posterior cingulate cortex (PCC) [126], and left hippocampus (HC) [127]. A study in of geriatric depression found reduced [tCr] in the PFC in persons with remitted depression compared to healthy controls [128].…”
Section: Methodsmentioning
confidence: 99%
“…BD has been associated with changes in [tCr]. It appears that [tCr] is reduced in several brain regions in BD, including in the frontal lobes [141], cerebellar vermis [142], hippocampi [143], caudate [144], medial PFC [145,146], dorsolateral PFC WM [146], and PCC [126], although some studies indicate that [tCr] is increased in BD in several brain regions [147,148,149]. Several studies have also failed to find alterations in [tCr], including in the left dorsolateral PFC [122,150,151] and ACC [152,153].…”
Section: Methodsmentioning
confidence: 99%
“…F18-fluorine-2-deoxy- d -glucose positron emission tomography can provide information regarding energy metabolism in the early stage of tumor formation [24]; however, this technique also has low specificity, high costs, and requires injection of radioactive substances [25]. Magnetic resonance spectroscopy is limited by its relatively poor detection sensitivity and poor spatial resolution in vivo [26, 27]. Moreover, the wide application of optical imaging is hindered by its intrinsic depth limitation [28].…”
Section: Introductionmentioning
confidence: 99%